Prevalence and risk factors of relationship dissatisfaction in women during the first year after childbirth: Implications for family and relationship counseling. - Khajehei, Marjan (2016)
The aim of this study was to investigate the rate of relationship dissatisfaction among Australian women during the first year after childbirth and to uncover factors affecting their relationships. Postnatal women who had given birth during the previous 12 months were invited to participate in a cross-sectional online study. A comprehensive, multisection questionnaire, as well as the Relationship Assessment Scale (RAS), Female Sexual Function Index (FSFI), and Patient Health Questionnaire - 8 (PHQ-8), were used to collect data. Responses were analyzed using SPSS for Windows. Results showed that 37.2% of the participants experienced relationship dissatisfaction. Results of the multiple logistic regression revealed that the following were significant risk factors for relationship dissatisfaction during the first postpartum year: annual income of less than AU $ 50,000, sexual dysfunction, and a clinical diagnosis of depression and having symptoms of depression according to the PHQ-8 scores (p < 0.05). Compared to women in a heterosexual relationship, women who were in a same- sex relationship were less likely to have relationship dissatisfaction. In addition, in the period six to 12 months postpartum, women were less likely to have relationship dissatisfaction compared to the period 5 months or less postpartum (p < 0.05).